Pengaruh Model Pembelajaran Numbered Head Together (THT) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XII IPS Swasta Taman Siswa Pematang Siantar - Syintia Agita Tarigan; Tumpal Manahara Siahaan; Herlina Hotmadinar Sianipar (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purposes of this research are to determine (1) the economic learning outcomes of class NHT learning model on student learning outcomes in economics subjects in class XII IPS Tamansiswa Private High School Pematang Siantar. This research method uses quantitative experimental methods. This research was carried out at Tamansiswa Pematang Siantar Private High School. The sampling technique in this research used purposive sampling and consisted of two classes, namely the experimental class and the control class, totaling 60 students. This data collection uses pre-test and post-test results in the form of multiple choice questions. The data analysis techniques used in this research are normality test, homogeneity test and t-test. Based on the findings in this research, it shows (1) the economic learning outcomes of students using conventional learning in the control class obtained an average score of 65. (2) the economic learning outcomes of students using the NHT learning model obtained an average score of 74.33. (3) there is an influence of the NHT learning model on the economic learning outcomes of students in class XII IPS at Tamansiswa Private High School Pematang Siantar. This is proven by the results of the t-test which obtained tcount > ttable = 4.53 > 1.68 with a significance level of 0.05, so it can be stated that ha is accepted. The conclusion of this research is the student learning outcomes in economic subject taught by using NHT learning model is better than using conventional learning in class XII IPS at Tamansiswa Private High School Pematang Siantar.